Thermal Decomposition Mechanisms of the Methoxyphenols: Formation of Phenol, Cyclopentadienone, Vinylacetylene, and Acetylene - Scheer, Adam M; Mukarakate, Calvin; Robichaud, David J; Nimlos, Mark R; Ellison, G. Barney (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2011)
The pyrolyses of the guaiacols or methoxyphenols (o-, m-, and p-HOC6H4OCH3) have been studied using a heated SiC microtubular (μ-tubular) reactor. The decomposition products are detected by both photoionization time-of-flight mass spectroscopy (PIMS) and matrix isolation infrared spectroscopy (IR). Gas exiting the heated SiC μ-tubular reactor is subject to a free expansion after a residence time of approximately 50–100 μs. The PIMS reveals that, for all three guaiacols, the initial decomposition step is loss of methyl radical: HOC6H4OCH3 → HOC6H4O + CH3. Decarbonylation of the HOC6H4O radical produces the hydroxycyclopentadienyl radical, C5H4OH. As the temperature of the μ-tubular reactor is raised to 1275 K, the C5H4OH radical loses a H atom to produce cyclopentadienone, C5H4O. Loss of CO from cyclopentadienone leads to the final products, acetylene and vinylacetylene: C5H4O → [CO + 2 HCCH] or [CO + HCC–CHCH2]. The formation of C5H4O, HCCH, and CH2CHCCH is confirmed with IR spectroscopy. In separate studies of the (1 + 1) resonance-enhanced multiphoton ionization (REMPI) spectra, we observe the presence of C6H5OH in the molecular beam: C6H5OH + λ275.1 nm → [C6H5OH Ã] + λ275.1nm → C6H5OH+. From the REMPI and PIMS signals and previous work on methoxybenzene, we suggest that phenol results from a radical/radical reaction: CH3 + C5H4OH → [CH3–C5H4OH]* → C6H5OH + 2H.